2006
DOI: 10.1136/bjsm.2006.027839
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin responses to a repeated bout of downhill running

Abstract: Objective: To examine the effect of downhill running on immunoglobulin responses. Method: Eleven untrained men performed 2 660 minute bouts of downhill running (213.5% gradient), at a speed eliciting 75% of their V O 2 PEAK on a level grade. Two runs were spaced 14 days apart. Serum samples were collected before, after, and every hour for 12 hours and every 24 hours for six days. Serum total creatine kinase and immunoglobulin isotypes and subclasses were measured, and results were analysed using a repeated mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…While a number of studies have reported a significant elevation in complement proteins after exercise, 24,25 the current study failed to elicit significant changes in complement C1-INH, C3 and C4. This finding was surprising considering that: (i) the participants were untrained; and (ii) research has previously shown that a similar exercise protocol is able to elicit significant elevations in immunoglobulins 26 and chemotactic cytokines. 27 In support of our findings, research has documented that certain complement proteins and complement regulatory proteins may not be affected by prolonged strenuous exercise.…”
Section: Discussionmentioning
confidence: 43%
“…While a number of studies have reported a significant elevation in complement proteins after exercise, 24,25 the current study failed to elicit significant changes in complement C1-INH, C3 and C4. This finding was surprising considering that: (i) the participants were untrained; and (ii) research has previously shown that a similar exercise protocol is able to elicit significant elevations in immunoglobulins 26 and chemotactic cytokines. 27 In support of our findings, research has documented that certain complement proteins and complement regulatory proteins may not be affected by prolonged strenuous exercise.…”
Section: Discussionmentioning
confidence: 43%
“…The first is a lack of data on many environmental exposures (e.g. tobacco smoke, physical exercise, parasitic infestation) which may modulate serum total IgE [30,31,32]. Parasites are well recognized to be strong stimulants of IgE production, although epidemiologic data suggests that helminthic infections are uncommon in westernized cities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to what has been observed for creatine kinase and other indirect markers of muscle damage. Overall, the surprisingly minor changes in com plement proteins, in response to a relatively severe bout of eccentric exercise suggests that either (a) little muscle damage was incurred (which based on cK responses [14] did not seem to be the case), or (b) changes in systemic complement protein concentration may not be sensitive markers of what is occurring in skeletal muscle. These results warrant further investigation as this is the first study to report such an effect and parti cipant numbers were limited.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the classical repeated bout effect being produced for creatine kinase (reported elsewhere [14]) the complement proteins failed to show the same phe nomenon. Recently, the study by Hubal et al [15] produced similar observations.…”
Section: Discussionmentioning
confidence: 99%